HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP IBU TENTANG PEMBERIAN KAPSUL VITAMIN A PADA BALITA : TINJAUAN LITERATUR - Hertati, Dessy; Natalia, Vita; Pratiwie, Nuning; Frisilia, Melisa (NHM PRESS, 2023)
Knowledge is an important factor in monitoring children's growth and development. The level of knowledge also greatly determines the mother's attitude in taking appropriate actions in caring for and educating children, especially in giving vitamin A to toddlers. Vitamin A is one of the important nutrients needed by toddlers during their growth and development. In the community itself, especially for mothers, the achievement of giving vitamin A to toddlers is still low due to the lack of mothers' level of knowledge about vitamin A and there are still mothers who do not take their children to the posyandu to get vitamin A. This research aims to determine the relationship between the level of knowledge and attitudes of mothers about giving vitamin A capsules to toddlers. This research method uses the literature review method. Search for journals using the Garuda portal and Google Scholar published in 2017-2020 using Indonesian. The research design used is Correlation Analysis. Of the 6 articles, 5 articles were found which had similarities showing that there was a relationship between the level of knowledge and the mother's attitude regarding giving vitamin A capsules to toddlers with the results of statistical tests from each article obtaining a p-value of 0.000 < 0.05. With a high level of knowledge, mothers can have a positive attitude in giving vitamin A and know the important benefits of vitamin A.